Proses Pengadopsian System Of Rice Intensification (SRI) oleh Anggota Subak Pacung di Desa Selat Kecamatan Abiansemal Kabupaten Badung - SUDARTANA, I WAYAN; PUTRA, I GEDE SETIAWAN ADI; SUARDI, I DEWA PUTU OKA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Adoption Process System Of Rice Intensification (SRI) By Member Of SubakPacung In The Villege Selat, The Abiansemal Region, Badung Regency Food Security is the availability of food and one's ability to access it. This studyaimed to determine the adoption of System of Rice Intensification (SRI) and theadopter category of Pacung Subak members. The research location wasintentionally determined in the village of Selat with a population of 50 people and asample of 24 people based on slovin formula and the data were analyzed withdescriptive analysis. The adoption process of SRI by Pacung Subak members at theconscious stage was 79.4%, at the interest stage it was 67.5%, at the judging stage,it was 80.2%, at the trying stage amounting to 80.3% to and at the adoption stage, itwas 40.2%. Adopter category Pacung Subak members, the Innovator class was 0%,early adopters was 13%, early majority was 54%, late majority was 33%, andlaggards amounted to 0%. In trying SRI, Subak members needs to do it over andover again so as to get good results. In addition, Subak members are expected toseek more information about SRI and the role of government is needed in thesuccessful adoption of an innovation that is given to farmers.
Keywords: food security; the process of adoption; members of Subak Pacung; System Of Rice Intensification